2004
DOI: 10.1074/jbc.m311395200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Structural Characterization of the Neuronal Luteinizing Hormone Receptor Associated with Sensory Systems

Abstract: The luteinizing hormone receptor (LHR) is a G protein-coupled receptor involved in regulation of ovarian and testicular functions. Here we show that the receptor is present also in specific areas of the peripheral and central nervous system and may thus have a broader functional role than has been anticipated. Full-length LHR mRNA and two receptor protein species of M r 90,000 and 73,000, representing mature and precursor forms, respectively, were expressed in adult and developing rat nervous tissue, starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 52 publications
3
64
0
2
Order By: Relevance
“…Whether such a regulatory role could be assigned to other splice variants of the LHR in general is not known. However, this is a very likely possibility, because changes in physiological stimuli (Lakkakorpi et al, 1993;Licht et al, 2003), cellular differentiation (Sokka et al, 1992;Tena-Sempere et al, 1994;Zhang et al, 1994;Apaja et al, 2004Apaja et al, , 2005 and tumorigenic cell growth (Lin et al, 1994;Reinholz et al, 2000;Jiang et al, 2002;Steinmeyer et al, 2003) have all been shown to regulate the splicing pattern of the receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether such a regulatory role could be assigned to other splice variants of the LHR in general is not known. However, this is a very likely possibility, because changes in physiological stimuli (Lakkakorpi et al, 1993;Licht et al, 2003), cellular differentiation (Sokka et al, 1992;Tena-Sempere et al, 1994;Zhang et al, 1994;Apaja et al, 2004Apaja et al, , 2005 and tumorigenic cell growth (Lin et al, 1994;Reinholz et al, 2000;Jiang et al, 2002;Steinmeyer et al, 2003) have all been shown to regulate the splicing pattern of the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody coupling was performed according to the instructions of the manufacturer using 50 l of antisera for 100 l of resin (Bio-Rad). Ligand affinity chromatography was performed using Affi-Gel 10 -coupled hCG, as described previously (Apaja et al, 2004). Glycerol 20% (vol/vol) was added to all buffers and 140 mM NaCl to buffer E instead of buffer B.…”
mentioning
confidence: 99%
“…The novel actions suggested include improvement of blastocysts implantation (Han et al, 1999), regulation of oviduct and cervix function (Lei et al, 1993a;Lin et al, 2003), improvement of endometrial angiogenesis and growth (Filicori et al, 2005), and a role in brain development and sexual behaviour (Lei et al, 1993b;Apaja et al, 2004). However, despite the numerous findings on existence of extragonadal LH/hCG-Rs their physiological significance has remained unclear, and in vivo evidence for their functionality and necessity is lacking.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…50,51 When this is taken into consideration along with the incomplete protection of hormone replacement therapy, it is evident that gender-specific, age-related changes in GnRH and the gonadotropic hormones may potentially play a role in the pathogenesis of AD. [52][53][54][55] Supporting a role for LH, as opposed to estrogen, in cognitive decline after menopause, studies have demonstrated that while cognitive decline can be rescued with estrogen therapy initiated immediately after ovariectomy, hormone replacement initiated after a long interval is ineffective.…”
mentioning
confidence: 99%